European Perspectives on Export Performance Determinants: an Exploratory Study - Lages, Luis Filipe (2019)
This exploratory study discusses main antecedents of export performance based on the perceptions of European export managers. Cross-national findings reveal that according to managerial perceptions the most important determinants of export performance are product quality, followed in importance by price competitiveness/value for money, service quality and relationship with importers/trust. While some of these determinants have been extensively researched in the literature (product and service quality), there are others in which there is limited empirical research (price competitiveness/value for money and relationship with importers/trust). Also of interest is the existence of specific issues that are not considered by managers as being top determinants, but are the focus of extensive research. Based on these findings the authors suggest several potentially fruitful streams of research.